Study on the Practice of Female Players’ Love Games from the Perspective of Gender and Communication: An Example of Light and Night - Xu, Xiuxiu (Transactions on Social Science, Education and Humanities Research, 2023)
In the electronic game market in China, the growing female player group and the increasingly popular female love games are strongly influencing the traditional gender pattern dominated by men in the field of electronic games. This paper takes the popular female love game Light and Night as the research object and analyzes the intrinsic motivation and behavioral characteristics of female players participating in the game, as well as the influence of the game on their love concept and love practice. It is found that female players participate in the game because their lack of self and love relationships in real life can be compensated in the game world. In the process of participating in the game, female players misappropriate the game text to perform participatory performances and use negotiated decoding to actively sort and construct the meaning of the game. Light and Night provides opportunities for female players to simulate love relationships and shape their love concepts, but it also causes their tendency to isolate themselves from real love. This paper holds that the female love games, represented by Light and Night, have a positive influence in promoting gender equality in the field of electronic games and giving female players the right to narrative and gaze.